Pengaruh Kepercayaan dan Customer value Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening pada Produk Sampo Lifebuoy - Apriani Wulandari; Rose Rahmidani (Jurnal Ecogen, 2022)
This study aims to determine the confidence of trust and customer value on customer loyalty through customer satisfaction as an intervening variable in Lifebuoy shampoo in the city of Padang. This type of research is causative research. The population in this study is the people of Padang city who have used Lifebuoy shampoo more than 2 times and the determination of the number of samples using the choachroan formula is as many as 97 samples. This study uses the purposive sampling technique with the consideration that consumers have used Lifebuoy shampoo more than 2 times. The data used is the type of primary data obtained through the distribution of questionnaires to the people of the city of Padang with predetermined criteria. The analytical method used is path analysis using SPSS 21. The results show that (1) trust has a significant and positive effect on customer satisfaction, (2) customer value has a significant and positive effect on customer satisfaction, (3) customer value significant and positive effect on customer loyalty, (4) customer satisfaction has a significant and positive effect on customer loyalty, (5) trust has a significant and positive effect on customer loyalty through customer satisfaction as an intervening variable, (6) customer value has a significant and positive effect on loyalty customers through customer satisfaction as an intervening variable.Keywords : trust, customer value, customer loyalty, and customer satisfaction